The implementation of project management practices in non-technical department - Nurzulaikha , Hashim (2014)
This research conducted aims to know whether the non-technical department applying project management practices and procedures, and appropriate tools used for handling and managing project. A theoretical framework has been developed in order to perform this research. Apart from that, the quantitative research methodology is used in conducting this research. Questionnaires were distributed to the management staff in 3 selected departments in Kuantan, Pahang. This research concludes that the department which implements the project management practices and procedures can lead the project successfully complete within the time and budget as stated by client. Apart from that, by implement project management practices and procedures the appropriate tools can be identified and applied in monitoring the project, and also can know how effectiveness its is in monitoring the project